Experimental study on user rating of virtual reality applications in manual order picking. Issue 13 (2019) - Elbert, Ralf; Knigge, Jan-Karl; Makhlouf, Rami; Sarnow, Tessa
Abstract: In recent years the use of virtual reality simulation for industrial purposes like product design, prototyping and employee training has rapidly increased. The cost efficient availability of devices like the HTC Vive has played into the rising amount of research done in this field. The technology is therefore especially interesting for the field of manual order picking. However, users´ rating of virtual reality in order picking in contrast to real world order picking has not yet been examined. The paper at hand therefore addresses this issue and tries to answer the following research questions: 1. How do the participants evaluate the general use of virtual reality technology and its aptitude for training purposes in order picking and does their rating change during the experimental study? 2. Does the rating of the use of virtual reality in order picking by the participants reflect their experimental results? To answer these questions an experimental study was conducted, in which 27 participants first had to pick orders in a virtual warehouse environment and afterwards in an identical real warehouse environment. In order to capture the participants´ evaluation, questionnaires were designed based on scientific approaches. The analysis of the given answers shows that the experimental study has a positive effect on users´ rating of virtual reality simulations in order picking. In conclusion the following article highlights the use of virtual reality simulation in this field and the potential of the technology for future research.